SRAP markers as an alternative tool for Alternaria classification - Castañares, Eliana; Dinolfo, Maria Ines; Patriarca, Andrea; Stenglein, Sebastian A. (Elsevier, 2023)
Alternaria is one of the main fungal contaminants of cereal grains worldwide with the potential to produce mycotoxins hazardous to human and animal health. Many studies have been carried out to characterize Alternaria sp.-grp. using traditional morphology or polyphasic approach, but a good correlation between morphological sp.-grp., molecular, and chemotaxonomic groups has not always been achieved. For this reason, this study aimed to investigate the usefulness of a cheaper alternative tool, SRAP markers, in identifying Alternaria sp.-grps. obtained from Argentinean barley grains and to compare it with preliminary characterization using morphological traits, phylogeny, and metabolite profiles. Fifty-three Alternaria isolates from barley grains of the main producing regions of Argentina were analyzed with four combinations of SRAP markers. The UPGMA dendrogram, based on the Simple Matching similarity coefficient, revealed three distinct groups. SRAP markers allowed the separation of Alternaria from Infectoriae sections in agreement with the results of a polyphasic approach previously made. Besides, isolates of A. arborescens sp.-grp. were clustered in a separate group from isolates of A. tenuissima and A. alternata sp.-grp., which were grouped in the same cluster. SRAP markers are a recommended tool for classifying Alternaria isolates because of its simplicity, reliability, and cost-effectiveness compared to other molecular markers.
Keywords: Alternaria; Characterizatio; Molecular marker; SRAP